ChemInform Abstract: The Structure of Tagetitoxin. Issue 17 (April 2016) - Aliev, Abil E.; Karu, Kersti; Mitchell, Robin E.; Porter, Michael J.
Abstract: Previously published structures of the potent title toxin are falsified.